PERAN TAX EFFORT PADA PENGARUH FLYPAPER EFFECT DAN FISCAL STRESS TERHADAP KINERJA KEUANGAN DAERAH KABUPATEN/KOTA DI PROVINSI ACEH - Fadhli Fadhli; Asnawi Asnawi; Jummaini Jummaini (Universitas Malikussaleh, 2022)
This study was to analyze of the significant effect or not of the effect of flypaper and financial stress on the financial performance of local governments with tax effort as a moderate variable. The data for this research were obtained from the DJPK in the form of the Regional Revenue and Expenditure Budget Achievement Report (APBD) as well as the supporting data in the form of the Revenue and Expenditure Budget. Regional budgets (APBD) and supporting data in the form of the Regional Revenue and Expenditure Budget (APBD). The GDP for Aceh Province is derived from the BPS in the Regency/City during the 2012-2021 period. Data analysis method was used is regression panel data with Eviews12 software. This study result was indicate that the flypaper effect has, in part, significant negative on local financial performance. Fiscal stress has a partially not significant negative on regional financial performance. Tax effort has a partially significant positive on regional financial performance. Tax effort can moderate the relationship between the flypaper effect on financial performance and then tax effort can moderate the relationship between the fiscal stress on financial performance of districts/municipalities in Aceh province.